2022
DOI: 10.3847/1538-4357/aca088
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of N+ Ion with H2, HD, and D2 at Low Temperatures: Experimental Study of the Pathway to Deuterated Nitrogen-containing Molecules in the Interstellar Medium

Abstract: This work is motivated by many observations of nitrogen hydrides including their isotopologues in the interstellar space. We studied the formation of NH+ and ND+ ions in the nearly thermoneutral hydrogen abstraction reactions of N+ ions with H2, HD, and D2 at temperatures from 300 K down to 15 K using a variable-temperature 22-pole radio frequency ion trap. For the reaction of N+ with HD, the branching ratios for production of ND+ and NH+ ions were also determined. The activation energies of all four reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…A notable result was obtained by Tosi et al (1994), who observed that the change of the energy threshold due to deuteration cannot be explained by the different zero-point energies of the deuterated species, suggesting that the energy threshold is not purely due to reaction enthalpy and an energy barrier is involved. On the other hand, several studies (Adams & Smith 1985;Marquette et al 1988;Plašil et al 2022), have observed isotope effects consistent with the hypothesis of no barrier. The recent study by Plašil et al (2022) shows that the available data are compatible with the hypothesis of no reaction barrier when only low-temperature thermal reaction rate coefficients with known error estimates are taken into account.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…A notable result was obtained by Tosi et al (1994), who observed that the change of the energy threshold due to deuteration cannot be explained by the different zero-point energies of the deuterated species, suggesting that the energy threshold is not purely due to reaction enthalpy and an energy barrier is involved. On the other hand, several studies (Adams & Smith 1985;Marquette et al 1988;Plašil et al 2022), have observed isotope effects consistent with the hypothesis of no barrier. The recent study by Plašil et al (2022) shows that the available data are compatible with the hypothesis of no reaction barrier when only low-temperature thermal reaction rate coefficients with known error estimates are taken into account.…”
Section: Introductionmentioning
confidence: 57%
“…On the other hand, several studies (Adams & Smith 1985;Marquette et al 1988;Plašil et al 2022), have observed isotope effects consistent with the hypothesis of no barrier. The recent study by Plašil et al (2022) shows that the available data are compatible with the hypothesis of no reaction barrier when only low-temperature thermal reaction rate coefficients with known error estimates are taken into account. The isotopic variation of activation energies in accordance with the hypothesis of the absence of energy barriers is a strong indication in favor of this hypothesis.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Anions formed in the SIS are periodically extracted and mass-selected by a quadrupole mass filter. Massselected anions are injected via a quadrupole bender into the 22PT ion trap (Gerlich et al 2013;Zymak et al 2013;Plašil et al 2022).…”
Section: Experiment-cryogenic Ion Trapmentioning
confidence: 99%